High efficient diode-pumped passively mode-locked Nd:LuAG laser - Xu, X. D. (2013)
A high efficient diode-pumped passively mode-locked Nd:Lu3Al5O12 (Nd:LuAG) laser is demonstrated with a semiconductor saturable-absorber mirror for the first time to our best knowledge. With an absorbed power of 10.5 W, a maximum output power of 1.05 W at 1064.4 nm was obtained, corresponding to an optical-optical conversion efficiency of 10% and a high slope efficiency of 60.2%. The mode-locked pulses have a pulse width of 5.4 ps. Our experimental results show that Nd:LuAG crystal could be an excellent alternative for high efficient diode-pumped passively mode-locked pulses generation.